Application of Protection Motivation Theory and Empowerment Program on Dengue Hemorrhagic Fever Control for Family Health Leaders in Tambon Pearram, Mueang District, Surin Province - ชูศรีขาว วรรณะ; ขามรัตน์ ชัยยง; วรสถิตย์ ไพศาล (Disease Control Journal, 2011)
Dengue hemorrhagic fever (DHF) was one of the important health problems across Thailand. At present DHF spreadec throughout every village of Thailand including Tumbon Paerram, Surin province. This quasi-experimental research aimed to explore the effects of Protective Motivational Theory and Empowerment Program for family health leaders on the Dengue hemorrhagic fever control. The study was carried out with family health leaders who were selected purposively from two villages. Sixty family health leaders participated in an experimental group receiving the Protective Motivational Theory interventions and the Empowerment Program, and the other 60 samples were in a comparison group. Data were collected by interview and survey which conducted before and after the experiment. Data were then analyzed using descriptive statistics and for testing hypothesis with the paired t-test and independent t-test. The results showed that the experimental group significantly gained knowledge of Dengue hemorrhagic fever, better perception of severity and risk of Dengue hemorrhagic fever, comply with protective recommendations,. The experiment group also showed these outcomes more than the comparison group (p<0.05). In addition, the larva index of the experimental village was lower than before conducting experiment program, and less than comparison village. In conclusion, the application of Protective Motivational Theory and the Empowerment Program had changed the knowledge, perception and practice in dengue hemorrhagic fever prevention of the participants. Therefore, the health organizations involved should apply the methodology for controlling and preventing Dengue hemorrhagic fever in other places of Surin province.